Optimization of the Use of Cow Manure as Natural Dyeing in Weaving Yarn - Neliyarti, Neliyarti; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (Science and Environmental Journal for Postgraduate, 2023)
This study aims to optimize the use of cow dung as a natural dye in woven yarn. The experimental method was used with several variations of treatment on samples of cotton threads which were to be colored with cow dung. The variables observed included the type and amount of auxiliary solution. The results showed that optimizing the use of cow dung as a natural dye could be done by selecting a certain type of auxiliary solution and giving the yarn the proper soaking time so that it could penetrate completely into the fiber. Under optimum conditions, the resulting color is quite strong and long-lasting, although not as bright as the color of synthetic dyes. Thus, the potential for the use of organic waste such as cow manure as a natural dye in the weaving industry should be considered. Law No. 32/2009 concerning Environmental Protection regulates the importance of reducing organic waste to maintain a healthy and sustainable environment.